Patterns of association between soil variables and land uses in the La Vieja River watershed, Colombia. - Feijoo-Martínez, Alexander; C. Zúñiga, Maria; Quintero, Heimar; Carvajal-Vanegas, Andrés F.; P. Ortiz, Diana (Instituto de Ecología, A.C., 2010)
In the Coffee Belt of Colombia we studied different patterns in land use considering the interaction between abundance, diversity and biomass of soil invertebrates (millipedes, beetles and earthworms), some physicochemical variables and land use intensity. Highest abundance and biomass of Coleoptera were found in Eucalyptus-lulo (Solanum quitoense), with 48 ind. m-2 and 9.4 g fresh weight (gfw) m-2, respectively. Millipede abundance and biomass was higher in the relict forest (53 ind. m-2 and 4.8 gfw m-2, respectively) and in the coffee variety Colombia (39.4 ind. m-2 and 3.1 gfw m-2, respectively). Earthworm abundance was higher in Eucalyptus-lulo (768 ind. m-2) and in the coffee variety Colombia (540 ind. m-2). Biological and physicochemical variables permitted the differentiation of three and four land use patterns, respectively. When they were combined with coinertia analysis, three patterns were distinguished, related to soil moisture, C and N contents and bulk density (p < 0.02). In pastures and the coffee variety Colombia, beetles (Ataenius sp., Onthophagus atriglabrus, Dichotomius satanas) and peregrine earthworms were dominant (Pontoscolex corethrurus, Polypheretima elongata, Dichogaster annae, Perionyx excavatus), soil C and N contents were low and bulk density higher. The analysis showed potential for separating biodiversity-friendly or biodiversity-critical areas and may be useful for land use planning in rural áreas.